Nutrition Status of Obstetric Outcomes in Pregnancy - Khoirunnisah Hasibuan; Sri Ratnaningsih (International Journal of Advanced Science and Technology, 2020)
Nutirional status is the reflection of the nutrition adequacy, this is one of the important parameters in assessing the growth and of health condition and is the indicators in measuring the success in fulfilling nutrition for mother during the pregnancy. The food needs is seen not only in the portion eaten, but also must be determined on the quality of nutrients contained in the food consumed. This paper reviews the evidence associated with the outcomes of obstetric nutritional status in pregnancy in LMICs. It uses the framework of Arskey and O’Malley, the focus of the review is determined, the search for articles with relevant database (PubMed, Science Direct and Wiley. Select relevant study by using some inclusion and exclusion criteria and conductiongcritical appraisal in order to assest the quality of the article, data extraction, data compilation, summarize and report the result. Twenty articles were selected according to inclusion criteria hadGrade A and B, two main themes were found from the result of the study; negative outcomes of excess and nutritional deficiencies in pregnancy for mothers and infants. In conclusion, the research results from articles used in scoping review show that most articles are on birth outcomes due to deficiency and excess nutrition in mothers in pregnancy which are the largest outcome, low birth weight (LBW), infant weight ˃ 4000 gram/ macrosomia, and babies with premature births. In addition, negative outcomes of excess and nutritional deficiencies in pregnancy also occur to mothers, that is that most mothers are obese or have high insulin levels.